2021
DOI: 10.1155/2021/8138374
|View full text |Cite|
|
Sign up to set email alerts
|

Gli1+ Cells Residing in Bone Sutures Respond to Mechanical Force via IP3R to Mediate Osteogenesis

Abstract: Early orthodontic correction of skeletal malocclusion takes advantage of mechanical force to stimulate unclosed suture remodeling and to promote bone reconstruction; however, the underlying mechanisms remain largely unclear. Gli1+ cells in maxillofacial sutures have been shown to participate in maxillofacial bone development and damage repair. Nevertheless, it remains to be investigated whether these cells participate in mechanical force-induced bone remodeling during orthodontic treatment of skeletal malocclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…They found that the calcium ion channel IP3R located on the endoplasmic reticulum was regulated by Gli + cells to promote osteogenesis. This study demonstrated that Gli1+ cells can sense mechanical forces and regulate calcium ion channels to modulate osteogenesis ( Huang et al, 2021 ). These reveal the specificity of Gli1+ in the process of skull reconstruction, providing a direction for skull reconstruction.…”
Section: Suture Mesenchymal Stem Cellsmentioning
confidence: 87%
“…They found that the calcium ion channel IP3R located on the endoplasmic reticulum was regulated by Gli + cells to promote osteogenesis. This study demonstrated that Gli1+ cells can sense mechanical forces and regulate calcium ion channels to modulate osteogenesis ( Huang et al, 2021 ). These reveal the specificity of Gli1+ in the process of skull reconstruction, providing a direction for skull reconstruction.…”
Section: Suture Mesenchymal Stem Cellsmentioning
confidence: 87%
“…Gli1 + cells gradually produce osteoblasts in all bone sites, and can mediate theTGF‐ß signaling pathway and play an important role in endochondral bone formation after fracture 28 . Some studies found that Gli1 + cells possess mechanical stress, which may regulate changes in intracellular Ca 2+ concentration through the inositol 1,4,5‐trisphosphate receptor (IP3R) to respond to mechanical force 29,30 . Compared with the above four genes, CLEC3B an CRABP2 have been less well studied in osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…28 Some studies found that Gli1 + cells possess mechanical stress, which may regulate changes in intracellular Ca 2+ concentration through the inositol 1,4,5-trisphosphate receptor (IP3R) to respond to mechanical force. 29,30 Compared with the above four genes, CLEC3B an CRABP2 have been less well studied in osteogenesis. CLEC3B is a major structural protein of the ocular lens and is abundant in the kidney, central nervous system, skeletal muscle and heart.…”
Section: Ta B L Ementioning
confidence: 99%
“…Other P2Y receptors (P2Y12-13-14) also have connections to osteoblast and/or osteoclast activity [ 85 , 86 , 87 , 88 ]; however, their intracellular signalling is not mediated by IP 3 R, at least not in a direct manner. IP 3 Rs are known players of osteoblast [ 89 ] and Gli1 + cell [ 90 ] intracellular Ca 2+ homeostasis. There is also indirect evidence pointing at the importance of Ca 2+ release from the ER store via IP 3 R during bone formation.…”
Section: Ion Channels Involved In Progenitor Cell Differentiationmentioning
confidence: 99%